Paciente de sexo masculino de 58 años de edad que presenta diabetes mellitus tipo 2 y obesidad grado 1 - Espín Fernández, Leydi Jacqueline (2020)
The present work details about the 58-year-old male patient who presents with Type II Diabetes Mellitus and Grade I Obesity, who goes to the medical office for presenting asthenia and adinamia with 2 weeks of evolution, personal pathological history: Diabetes Mellitus Type II for 13 years, with relevant family pathological antecedents: Living Diabetic Mother, receives Dialysis treatment. The main objective is to intervene nutritionally to the patient according to nutritional needs and pathologies, taking into account their anthropometric, biochemical, clinical and dietary parameters which leads us to make a comprehensive nutritional diagnosis and therefore provide an adequate treatment adjusted to the nutritional needs of the patient to help improve their quality of life. The research carried out by the National Health and Nutrition Survey in 2013 showed that more than 400,000 people, between 10-59 years old, suffer from diabetes. Among them, about 90% have insulin resistance and among non-diabetics almost one in two have the same problem. More than 900 thousand people between 10 and 59 years of age have abdominal obesity, which is one of the determining factors of coronary heart disease and more than 50% of them have metabolic syndrome (National Survey of Health and Nutrition, 2013). Tobacco use, physical inactivity, unhealthy diets and the harmful use of alcohol increase the risk of most NCDs or cause them directly. These risks lead to four key metabolic / physiological changes for the development of NCDs: high blood pressure, overweight / obesity, hyperglycemia (high blood glucose levels) and hyperlipidemia (high blood lipid levels) called intermediate risk factors. and are in themselves important causes of demand for health care (WHO & PAHO, 2014, p. 16).